Overexpression of microRNA-133b reduces myocardial injuries in children with viral myocarditis by targeting Rab27B gene - Zhang, Y.; Sun, L.; Sun, H.; Liu, X.; Luo, X.; Li, C.; Sun, D.; Li, T. (Cellular and Molecular Biology, 2017)
The present study is to measure the expression of microRNA (miRNA or miR)-133b in circulating blood of children with viral myocarditis before and after drug treatment, and to investigate its relationship with the severity of myocardial lesions. A total of 36 children patients with viral myocarditis who received treatments at our hospital between June 2014 and June 2016 were enrolled in the present study, including 21 boys and 15 girls (age range, 9 months – 16 years).Quantitative real-time polymerase chain reaction was used to determine the expression of miR-133b in peripheral blood of patients and cardiomyocytes infected with CVB3. CCK-8 assay was used to test the proliferation of cardiomyocytes. ELISA was used to determine the levels of creatine kinase (CK-MB) and lactate dehydrogenase (LDH) in peripheral blood and cardiomyocyte culture supernatants. Western blotting and ELISA were performed to measure the levels of tumor necrosis factor-Î± and interleukin-6 in cardiomyocytes infected by CVB3 and cell culture supernatants. Bioinformatics was used to predict the target gene of miR-133b. Silencing of Rab27B gene was achieved by transfection with its small-interfering RNA. Dual luciferase reporter assay was carried out to test whether miR-133b directly targets Rab27B. Reduced expression of miR-133b in peripheral blood was possibly correlated with myocardial injuries in viral myocarditis miR-133b. Expression of miR-133b was significantly reduced in cardiomyocytes infected with CVB3 virus. Overexpression of miR-133b inhibited cardiomyocyte injuries caused by CVB3 virus infection, and the enhanced production and release of cytokines TNF-Î± and IL-6 by cardiomyocytes infected with CVB3 virus. Rab27B promoted injuries of cardiomyocytes induced by CVB3 infection and facilitated the synthesis and release of cytokines TNF-Î± and IL-6 by cardiomyocytes. miR-133b was able to bind to the 3’-untranslated region seeding region of Rab27B mRNA. The present study demonstrates that expression of miR-133b in peripheral blood from children with viral myocarditis is reduced, and negatively correlated with myocardial injuries. miR-133b inhibits the proliferation of cardiomyocytes and the release of cytokines TNF-Î± and IL-6, and alleviates CVB3 infection-induced myocardial injuries by targeting Rab27B.